Higher Order Thinking in the Content Knowledge of History Lesson in Malaysia - Dahalan, Shakila Che; Ahmad, Abdul Razak; Seman, Ahmad Ali (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
This study investigating student’s achievement on the higher order thinking content knowledge in history lesson. A total of 200 upper secondary school students were given 40 objectives questions on higher order thinking content knowledge. The higher order thinking content knowledge was analysis using SPSS 24.0. The results showed that student’s application (f=54.8, %=75.1), analysis (f=40.8, %=55.9) and evaluation (f=40.2, %=55.0). The findings indicate that student’s achievement on the higher order thinking content knowledge (application, analysis and evaluation) in medium level. Therefore, the findings highlight the important of teacher in improving their pedagogy of teaching and change their focusing to higher order thinking in history education.